2017
DOI: 10.3171/2016.3.jns152846
|View full text |Cite
|
Sign up to set email alerts
|

Reappearance of arteriovenous malformations after complete resection of ruptured arteriovenous malformations: true recurrence or false-negative early postoperative imaging result?

Abstract: OBJECTIVE Ruptured arteriovenous malformations (AVMs) are often obliterated after emergency microsurgical treatment. However, some studies have reported AVM recurrence after the obliteration of ruptured AVMs. The authors report their experience with AVM recurrence after successful microsurgical treatment of ruptured AVMs. METHODS The authors reviewed the medical data of 139 consecutive patients who underwent microsurgery at the authors' institution for ruptured AVM between 2002 and 2012. Each patient underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…446 In all cases, long-term follow-up, including posttreatment DSA, is critical because recurrence rates are as high as 11%. 447,448 Typically, a perioperative and 1-year postoperative DSA may be considered, followed by MRI/MRA annually for up to 5 years. 439,441,448 Arteriovenous Fistula Imaging.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…446 In all cases, long-term follow-up, including posttreatment DSA, is critical because recurrence rates are as high as 11%. 447,448 Typically, a perioperative and 1-year postoperative DSA may be considered, followed by MRI/MRA annually for up to 5 years. 439,441,448 Arteriovenous Fistula Imaging.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…Recently, Aboukaïs et al analyzed the subject and reported the recurrence as a fairly rare case (7/138 cases) affecting mostly pediatric patients. They recommend particularly long-term angiographic follow-up in children to detect AVM recurrence or remnants [96].…”
Section: Results and Complicationsmentioning
confidence: 99%
“…Complete excision of the bAVM nidus with obliteration of arteriovenous shunting is required to eliminate the risk of hemorrhage. Although there is little in the neurosurgical literature about recurrent bAVMs, with sporadic case reports and series describing bAVM recurrence after angiographic confirmation of obliteration, [27][28][29] they are likely more common than previously thought. A recent meta-analysis of this literature showed that bAVM recurrence occurred in 2.7% of reported adult series and in nearly 10%-15% of children.…”
Section: Discussionmentioning
confidence: 98%